Frauds, myths, and mysteries : - Feder, Kenneth L. (McGraw-Hill, 2006)
Ancient astronauts? Atlantis? Psychic archaeology? Pharaoh’s curses? Committed to the scientific investigation of human antiquity, this indispensable supplementary text uses interesting archaeological hoaxes, myths, and mysteries to show how we can truly know things about the past through science. The text presents examples of fantastic findings, and carefully, logically, and entertainingly describes the flaws in the purported evidence for each fantastic claim; readers can hone their own evaluative skills by example.